Jigsaw-Type Cooperative Learning in Improving Basic Electrical Learning Outcomes of Students of SMKN 2 Bitung - Maasje Elungan; Eklesiano Lamo; Fransiskus Seke; Billy Kilis; Nontje Sangi (JURNAL EDUNITRO Jurnal Pendidikan Teknik Elektro, 2024)
This research is classroom action research that aims to improve the learning process by applying the jigsaw-type cooperative learning model to improve Basic Electrical learning outcomes for Class X TITL students at SMK Negeri 2 Bitung, carried out in March 2021. Techniques and data collection tools in this research used descriptive statistical analysis of the data in student test results from documents and a list of scores. This study uses two stages of the cycle where the first cycle consists of IV meetings and the second cycle consists of IV meetings. Cycle I students achieve 55% incomplete and 45% complete learning outcomes. Cycle II students achieve 0% incomplete and 100% complete learning outcomes. The increase in learning outcomes was seen in the second cycle, namely the results of student learning achievement of 100% complete from the number of 20 students. Thus, learning using the jigsaw-type cooperative learning model can improve the learning outcomes of class X TITL students at SMK Negeri 2 Bitung.